Review of Past Efforts on Housing Typologies Supply, Demand and Needs in Response to Public Housing Estimates in Awka Capital Territory, Anambra State - Okafor Iwuchukwu (JOURNAL OF HOTEL MANAGEMENT AND TOURISM RESEARCH, 2026)
Anambra state went through two stages of historical existence. The first stage of historical existence was in 1976, when she was carved our East Central Stages later in 1991, to become separate with two states emerging, Anambra and Enugu, Precisely, in 1992, a new law was enacted, titled, Anambra State Housing Development Cooperation cap 67. Giving the cap, all existing housing estates in the new Anambra State came under the Management of ASHDC. Among the housing estates in Akwa Capital territory included, UDOKA housing estate, with 450 housing units in PHASE I and 519 dwelling units in PHASE II, others include, NGOZIKA; 1000, dwelling unto, Liberation Housing Estate, 726 dwelling units. Correspondingly, investigation revealed that demand for housing shall outstrip supply hence, the reed, to develop more estates.